ChatGPT in Academic Writing: A Threat to Human Creativity and Academic Integrity? An Exploratory Study - Inuusah Mahama; David Baidoo-Anu; Peter Eshun; Benjamin Ayimbire; Veronic Esinam Eggley (CV. Literasi Indonesia, 2023)
OpenAI ChatGPT has become the most popular academic writing software due to the kind of responses it gives, being seen as a replacement for much of the daily mundane writing, from emails to even college-style essays. As generative software, ChatGPT has caught the attention of everyone from business and policy stakeholders, signaling a paradigm shift in artificial intelligence. Despite ChatGPT’s popularity and appeal in academic writing, there are fears regarding its consequences for human creativity and academic integrity. The study employed critical literature review analysis to explore the importance of ChatGPT in academic writing, its effects on human creativity and academic integrity, and suggestions for proper adoption and application. In the review process, it was revealed that ChatGPT is important in improving the learning and academic outcomes of diverse professionals and learners. However, the review suggests that the responses or outputs from ChatGPT sometimes are inaccurate and misleading. Therefore, implications for policy and practice were discussed.